GENETIC ASSOCIATION STUDIES OF FIBROMUSCULAR DYSPLASIA IDENTIFY NEW RISK LOCI AND SHARED GENETIC BASIS WITH MORE COMMON VASCULAR DISEASES. (April 2021) - Georges, Adrien; Yang, Min-Lee; Berrandou, Takiy-Eddine; Bakker, Mark; Dikilitas, Ozan; Ma, Lijiang; Satterfield, Benjamin A.; Sengupta, Sebanti; Hunker, Kristina L.; Amar, Laurence; Lorthioir, Aurélien; Prejbisz, Aleksander; et al.
Abstract: Objective: Fibromuscular dysplasia (FMD) is an arteriopathy that presents mainly by hypertension, stroke or dissection. Diagnosis is often made in middle-aged women with few cardiovascular risk factors. We aim at identifying common genetic variants associated to FMD. Design and method: We tested ∼6.5 million common genetic variants (MAF > 0.01) in 1962 cases and 7100 controls from 6 studies using variants and gene-based association analyses. Participants were of European ancestry, with similar characteristics (91% multifocal, 88% women), diagnosis methods and inclusion/exclusion criteria. Transcriptome-wide association (TWAS), eQTL, gene expression by sex and colocalization analyses used expression data in arteries from GTEx and/or FMD patients and matched controls. Open chromatin regions were defined using ATAC-Seq on primary human fibroblasts, smooth muscle and endothelial cells. Genetic correlations were assessed using summary statistics from UKBiobank and/or published studies by linkage disequilibrium score regression and multi-trait-based conditional and joint analyses (mtCOJO). Figure. No caption available. Results: We confirmed the previously identified PHACTR1 locus and identified three new loci (LRP1, ATP2B1, and LIMA1) associated with FMD. TWAS in arteries identified one additional locus (SLC24A3). Through integration of annotation datasets, we provided prioritization of variants and genes. These are consistently and specifically expressed in fibroblasts, smooth muscle cells, and arterial tissues. PHACTR1 and SLC24A3 showed sex differences in gene expressions consistent with the direction of effects of FMD risk alleles. FMD genes are involved in regulatory mechanisms related to actin cytoskeleton and intracellular calcium homeostasis, two mechanisms central to vascular contraction. We found significant genetic overlaps between FMD and blood pressure traits, for the associated loci and globally at the genome level, but demonstrated that hypertension is not driving the genetic association with FMD. We also found positive genetic correlations with migraine and intracranial aneurysm, and an inverse correlation with coronary artery disease, independently from the genetics of blood pressure. Conclusions: We describe robustly associated loci and genes with FMD and provide several new leads toward understanding biological mechanisms of stenosis and dissection in young women in the absence of atherosclerosis, which shares part of its genetic basis with more common cardiovascular and neurovascular diseases.